In-vivo mineralization self-growth method of double-layer protective coating, corresponding double-layer protective coating and preparation method of double-layer protective coating
Through the in vivo mineralization self-growth method of the double-layer protective coating, the mineralization factor release layer and the mineral growth promotion layer are used to solve the problem of excessive degradation of magnesium-based medical devices, and long-lasting protection and good biocompatibility are achieved.
Patent Information
- Application Number
- CN202510200694.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-24
AI Technical Summary
Magnesium-based medical devices degrade too quickly in the body, resulting in local high pH, hydrogen production, and loss of mechanical properties, affecting histocompatibility and bone repair effects, and traditional coating technology cannot provide long-lasting protection.
The in vivo mineralization self-growth method is adopted with a double-layer protective coating. The first layer is a mineralization factor release layer and the second layer is a mineral growth promotion layer. The biomineralization of calcium and phosphorus is promoted by releasing the mineralization factors in the body fluids, forming a stable and dense mineral protection layer.
It achieves long-lasting protection of magnesium-based materials, extends the protection time of the coating, enhances biocompatibility and biological activity, adapts to the corrosive environment of body fluids, and avoids the problems of local high pH and hydrogen production.
Smart Images

Figure CN119656395A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of medical implantable medical devices such as stomatology, orthopedics, and heart stents, and in particular relates to an in vivo mineralization self-growth method of a double-layer protective coating, a double-layer protective coating and a preparation method thereof. Background Art
[0002] Magnesium metal and its alloys have shown broad application prospects in the fields of medical implants such as dentistry, orthopedics and heart stents due to their mechanical properties similar to those of bone tissue, good biocompatibility, and biodegradable properties. However, due to the low reduction potential and active nature of magnesium-based metals, they are corroded by body fluids after implantation in the human body, causing a rapid and uncontrollable degradation rate, further causing problems such as local high pH, hydrogen production, and premature loss of mechanical properties, affecting the tissue compatibility and bone repair effect of magnesium-based metals, and even bringing safety hazards such as tissue necrosis, which greatly limits their further clinical application transformation. Up to now, surface coating technology is still considered to be a direct and effective means to regulate the degradation rate of magnesium-based metals. And when bioactive materials are selected as coating materials, while controlling the degradation rate, they also give magnesium-based materials certain biological functionality, achieving greater clinical application value.
[0003] However, traditional organic coatings (such as polylactic acid, polycaprolactone, etc.) have inherent defects such as poor ability to promote bone tissue regeneration and weak interface bonding with magnesium metal. They are also prone to produce acidic substances after degradation in the body, further exacerbating the corrosion of magnesium metal. Therefore, traditional organic coatings are not an ideal choice for magnesium-based metal coating technology.
[0004] Prior art DE10143410A1 discloses a method of forming synthetic apatite by depositing hydroxyapatite particles on a metal surface, which can improve sufficient bonding strength and incorporate hydroxyapatite into an organic phase in a characteristic form of biomineralization. Prior art CN111973812A discloses a biodegradable magnesium-based bone implant surface with a biologically active, hierarchical hydroxyapatite coating and a preparation method, wherein the coating comprises an inner fluoride film and an outer hydroxyapatite conversion coating. The method first immerses magnesium and magnesium alloys in hydrofluoric acid to generate a chemical conversion film MgF2, then immerses them in a calcium phosphate solution, and generates a brushite coating by chemical deposition; finally, a hydrothermal conversion method is used to in-situ convert the brushite coating into a thicker hydroxyapatite coating with a composite surface morphology of a micro-nano hierarchical structure under high temperature and pressure, which can improve the corrosion resistance and biological activity of the magnesium substrate. However, although traditional inorganic coatings have advantages in bone bonding and mechanical properties, due to their high brittleness, they are prone to internal defects such as cracks during surgeries such as screw implantation and bending, which in turn cause the infiltration of corrosive body fluids and trigger rapid corrosion of the magnesium metal substrate. Therefore, they cannot provide long-term and effective protection.
[0005] In order to extend the protection time of the coating, the strategy of "self-healing anti-corrosion coating" has also been proposed. This strategy prevents further corrosion by loading anti-corrosion (or self-healing) agents into the coating skeleton and releasing them responsively after the coating is damaged. However, since the loaded anti-corrosion agents (or self-healing agents) are usually consumed over time and cannot be effectively replenished in the body, and there are problems such as potential toxicity, the long-term reliability and biosafety of this strategy still face huge challenges. Summary of the invention
[0006] In order to overcome the technical problems existing in the above-mentioned prior art, the present invention proposes an in vivo mineralization self-growth method of a double-layer protective coating based on the innovative "in vivo mineralization self-growth coating" strategy, as well as the corresponding double-layer protective coating product and its preparation method.
[0007] Specifically, the present invention first provides an in vivo mineralization self-growth method for a double-layer protective coating, which includes a double-layer protective coating based on magnesium-based metals, wherein the first layer of the double-layer protective coating is a mineralization factor releasing layer, and the second layer is a mineral growth promoting layer. After the double-layer protective coating is implanted into the human body, the mineralization factors in the mineralization factor releasing layer are released into the body fluid environment, promoting the biomineralization of calcium and phosphorus in the body fluid environment, and continuously depositing and mineralizing in the mineral growth promoting layer, and converting into new minerals. The new minerals continuously fill the defects in the second layer, and finally form a stable and dense coating in the corrosive body fluid, which provides long-lasting protection for the magnesium-based metal.
[0008] Furthermore, the mineralization promoting factor in the present invention may be fluoride ions, the first mineralization promoting factor releasing layer may be a porous MAF layer formed on the surface of the magnesium-based metal by the micro-arc fluorination MAF process, and the second mineral growth promoting layer may be a fluorohydroxyapatite FAP layer.
[0009] Correspondingly, the present invention also proposes a double-layer protective coating, wherein the first layer is a mineralization-promoting factor-releasing layer, and the second layer is a mineral growth-promoting layer.
[0010] Furthermore, the mineralization-promoting factor-releasing layer is a porous MAF layer formed on the surface of the magnesium-based metal by a micro-arc fluorination MAF process, and the mineral growth promoting layer can be a fluorohydroxyapatite FAP layer.
[0011] Furthermore, the MAF layer is a coral-like porous structure with a thickness of 0.5 to 9 microns, preferably 3 to 5 microns, and the main component is MgF2.
[0012] Furthermore, in the fluorohydroxyapatite FAP layer, the FAP nanorods can be assembled FAP-P substantially parallel to the surface of the MAF layer, or the FAP nanorods can be assembled FAP-V substantially perpendicular to the surface of the MAF layer, and the FAP layer and the MAF layer form an inter-embedded structure.
[0013] Since there are certain errors in the vertical or horizontal direction during generation, substantially parallel and substantially vertical mean that they are roughly vertical or parallel, but there may be certain errors or slight deviations.
[0014] Correspondingly, the present invention also proposes a method for preparing a double-layer protective coating, the specific process of which is as follows:
[0015] (1) Preparation of MAF layer: A porous MAF layer is formed on the surface of magnesium-based metal through the MAF process. The main component of the porous MAF layer is MgF2.
[0016] (2) Preparation of FAP layer: Nanoapatite NanoHAP seed crystals are adsorbed on the surface of the MAF layer and placed in a mineralizing solution. The adsorption amount of the seed crystals, the temperature and time of the mineralization reaction are controlled to control the formation of a FAP layer microstructure on the MAF layer.
[0017] Furthermore, the method for preparing the MAF layer also includes:
[0018] (1) Use laser to cut magnesium sheets into discs with handles. The discs can be Ø16×1.5 mm, Ø8×0.5 mm, Ø6×0.5 mm, or other sizes.
[0019] (2) The disc was ground and polished step by step with #1000 and #2000 silicon carbide papers, cleaned with anhydrous ethanol, and air-dried at room temperature.
[0020] (3) The polished magnesium disk with a supporting tail was used as the anode and the graphite rod was used as the cathode, which were immersed in a polytetrafluoroethylene (PTFE) container filled with 46% hydrofluoric acid and subjected to micro-arc fluorination in a DC constant voltage mode;
[0021] (4) After the MAF process is completed, the samples are washed with deionized water and ethanol in turn and dried at room temperature.
[0022] Preferably, the conditions of the micro-arc fluorination MAF process are: when the sample is a disk with a size of Ø16×1.5 mm, in the constant voltage DC mode: the voltage is 180~210 V, preferably 185~195 V; the current is 150~165 mA, and as the diameter of the sample changes, the voltage remains unchanged, and the current decreases proportionally with the contact area.
[0023] Furthermore, the method for preparing the FAP layer further includes:
[0024] (1) Immerse the MAF layer in the NanoHAP suspension.
[0025] (2) The MAF sample was soaked in NanoHAP dispersion for 5-40 min, then taken out and immersed in mineralization solution for mineralization after the surface level evaporated.
[0026] The concentration of the NanoHAP suspension can be determined according to the amount of the crystal seed layer to be adsorbed and deposited, and is more preferably 2% NanoHAP deionized water dispersion.
[0027] Furthermore, 1% gelatin may or may not be added as a dispersant.
[0028] Furthermore, in the fluorohydroxyapatite FAP layer, the FAP nanorods can be assembled FAP-P substantially parallel to the surface of the MAF layer, or the FAP nanorods can be assembled FAP-V substantially perpendicular to the surface of the MAF layer.
[0029] Among them, the synthesis conditions for assembling FAP-P with FAP nanorods substantially parallel to the surface of the MAF layer are: after NanoHAP seeds are deposited, they are grown in a mineralizing solution at 12-17°C, preferably at 15°C, for 2-8 hours, preferably 3 hours, and then washed with deionized water and dried at room temperature.
[0030] The synthesis conditions for assembling FAP-V with FAP nanorods substantially perpendicular to the MAF surface are as follows: NanoHAP seeds are deposited and grown in a mineralizing solution at 37° C. for 2-8 hours, preferably 3 hours, and then washed with deionized water and dried at room temperature.
[0031] Compared with the prior art, the present invention has at least the following beneficial effects:
[0032] The present invention proposes a method for in vivo mineralization self-growth of a double-layer protective coating, which continuously releases mineralization-promoting factors into body fluids to promote biomineralization, and then dynamically and in situ converts the abundant "calcium source" and "phosphorus source" in the body fluids into a mineral protective layer on the surface of the magnesium metal under in vivo biomineralization. Through reasonable structural design, new minerals will continuously deposit inside the coating, repair internal defects of the coating, and maintain the density and integrity of the coating. Since the new minerals are spontaneously generated in the body fluid environment, they can better adapt to the body fluid corrosion environment and maintain good stability in the body fluid, thereby achieving durable and adaptive protection of magnesium-based metals in complex body fluid corrosion environments. Similarly, since the self-growing protective layer grows and forms in the body environment, the self-growing coating has good biocompatibility and biological activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1It is a design concept diagram and a schematic diagram of the mineralization self-growth method in vivo of the double-layer protective coating proposed by the present invention.
[0034] Figure 2 is a characterization diagram of the MAF coating in the present invention, Figure 2 Middle: A is the XRD pattern; B is the cross-sectional SEM and EDS pattern; C and D are SEM cross-sectional patterns.
[0035] Figure 3 is a schematic diagram of the FAP / MAF double-layer coating of the present invention, Figure 3 Middle: A is a schematic diagram of the synthesis preparation process; B is the SEM photo of the surface morphology of MAF, FAP-P / MAF, and FAP-V / MAF coatings; C is the SEM cross-sectional photo of the surface morphology.
[0036] Figure 4 It is a characterization diagram of the FAP / MAF double-layer coating in the present invention. Figure 4 Middle: A is the ratio of the number of Ca and P atoms in FAP-P and FAP-V coatings; B is the XRD curves of FAP-P / MAF and HAP-V / MAF coatings; C is the ATR-FTIR curves of FAP-P / MAF and FAP-V / MAF coatings.
[0037] Figure 5 It is a characterization diagram of ordinary MgF2 coating at different magnifications after 3 hours of mineralization growth in the comparative example of the present invention.
[0038] Figure 6 This is a test result diagram of the bonding performance of the double-layer coating in the present invention. Figure 6 Middle: A is the scratch test result; B is the statistical diagram of the coating interface bonding force.
[0039] Figure 7 It is a statistical diagram of the release of F ions from the MAF coating of the present invention.
[0040] Figure 8 This is a comparison chart of the effects of F ions in the present invention on promoting the regrowth and densification performance of the FAP-P layer. Figure 8 Middle: A is the SEM surface morphology of the glass slide after the FAP-P coating was deposited on the glass slide and then immersed in α-MEM culture medium without fluorine for 3 days; B is the SEM surface morphology of the glass slide after it was immersed in α-MEM culture medium containing 10 ppm fluorine for 3 days.
[0041] Fig. 9 It is a comparison diagram of the effects of in vitro mineralization, regrowth and densification of the FAP-P / MAF layer in the present invention.
[0042] Fig.10 This is a characterization diagram of the in vitro mineralization regrowth and composition changes of the FAP-P / MAF coating of the present invention. Fig.10Middle: A is the XRD spectrum of the coating of the FAP-P / MAF sample after subcutaneous implantation for 1 week, 4 weeks, and 8 weeks; B is the TEM-EDS element distribution of the FAP particles after the FAP-P / MAF sample was subcutaneously implanted for 4 weeks.
[0043] Fig.11 It is a comparison diagram of the effects of in vitro mineralization, regrowth and densification of the FAP-V / MAF layer in the present invention.
[0044] Fig.12 This is a characterization diagram of the in vitro mineralization regrowth and composition changes of the FAP-V / MAF coating of the present invention. Fig.12 Middle: A is the XRD spectrum of the coating after the FAP-V / MAF sample was subcutaneously implanted for 1 week, 4 weeks, and 8 weeks. B is the TEM-EDS element distribution of the FAP particles after the FAP-V / MAF sample was subcutaneously implanted for 4 weeks.
[0045] Fig.13 It is a comparison chart of the in vitro anti-corrosion performance of the FAP / MAF coating of the present invention. Fig.13 Middle: A is the Taffel curve of pure magnesium and magnesium metal modified with different coatings in simulated body fluid; B is the impedance curve of pure magnesium and magnesium metal modified with different coatings in simulated body fluid; C: is the hydrogen evolution curve of magnesium metal modified with different coatings in simulated body fluid; D is the Mg ion release curve of magnesium metal modified with different coatings in α-MEM culture medium (containing protein).
[0046] Fig.14 It is a characterization of the in vivo mineralization self-growth performance of the FAP-P / MAF coating in the present invention. Fig.14 Middle: A is a schematic diagram of the in vivo subcutaneous implantation model; B is a SEM comparison of the cross-sectional morphology of HAP-P before and after 4 weeks of implantation; CE is FIB-TEM characterization of the internal structure of FAP-P / MAF after 4 weeks of in vivo implantation; F is TEM-EDS characterization of the changes in the Ca / P ratio and F / Ca ratio of the FAP-P coating before and after 4 weeks of in vivo implantation.
[0047] Fig.15 This is a comparison of the in vivo mineralization self-growth morphologies of different implant samples in the present invention after 4 weeks of implantation.
[0048] Fig.16 This is a graph showing the results of the in vivo corrosion protection performance of the FAP / MAF coating of the present invention. Fig.16 Middle: A is the corrosion depth of pure magnesium metal at different implantation times; B. is the corrosion depth of magnesium metal modified with different coatings changing with time. DETAILED DESCRIPTION
[0049] The in vivo mineralized self-growing protective coating and its preparation method in the present invention are further described below in conjunction with the accompanying drawings in the examples of the present invention. The following examples are only used to illustrate the present invention and are not intended to limit the present invention.
[0050] like Figure 1 As shown, the present invention first provides an in vivo mineralization self-growth method for a double-layer protective coating, which includes a double-layer protective coating based on magnesium-based metals, wherein the first layer of the double-layer protective coating is a mineralization factor releasing layer, and the second layer is a mineral growth promoting layer. After the double-layer protective coating is implanted into the human body, the mineralization factors in the mineralization factor releasing layer are released into the body fluid environment, promoting the biomineralization of calcium and phosphorus in the body fluid environment, and continuously depositing and mineralizing in the mineral growth promoting layer, and converting into new minerals. The new minerals continuously fill the defects in the second layer, and finally form a stable and dense coating in the corrosive body fluid, which provides lasting protection for the magnesium-based metal.
[0051] Furthermore, the mineralization promoting factor in the present invention may be fluoride ions, the first mineralization promoting factor releasing layer may be a porous MAF layer formed on the surface of the magnesium-based metal by the micro-arc fluorination MAF process, and the second mineral growth promoting layer may be a fluorohydroxyapatite FAP layer.
[0052] Correspondingly, the present invention also proposes a double-layer in vivo mineralization self-growth protective coating, which has a double-layer structure, wherein the first layer is a mineralization-promoting factor release layer, and the second layer is a mineral growth-promoting layer.
[0053] Furthermore, the mineralization-promoting factor-releasing layer may be a porous MAF layer formed on the surface of the magnesium-based metal by a micro-arc fluorination MAF process, and the mineral growth-promoting layer may be a fluorohydroxyapatite FAP layer.
[0054] Furthermore, the MAF layer is a coral-like porous structure with a thickness of 0.5 to 9 microns, preferably 3 to 5 microns, and the main component is MgF2.
[0055] Furthermore, in the fluorohydroxyapatite FAP layer, the FAP nanorods can be assembled FAP-P substantially parallel to the surface of the MAF layer, or the FAP nanorods can be assembled FAP-V substantially perpendicular to the surface of the MAF layer.
[0056] Since there are certain errors in the vertical or horizontal direction during generation, substantially parallel and substantially vertical mean that they are roughly vertical or parallel, but there may be certain errors or slight deviations.
[0057] Correspondingly, the present invention also proposes a method for preparing a double-layer in vivo mineralized self-growing protective coating, the specific process of which is as follows:
[0058] (1) Preparation of MAF layer: A porous MAF layer is formed on the surface of magnesium-based metal through the MAF process, and the composition of the porous MAF layer is MgF2;
[0059] (2) Preparation of FAP layer: Nanoapatite NanoHAP seed crystals are adsorbed on the surface of the MAF layer and placed in a mineralization solution. The temperature and time of the mineralization reaction are controlled to form a FAP layer on the MAF layer.
[0060] Furthermore, in the preparation process, by controlling different reaction temperatures, FAP layers with different morphologies can be formed. By regulating the reaction time, the thickness, density and other microstructures of the FAP layer can be controlled.
[0061] Furthermore, the method for preparing the MAF layer also includes:
[0062] (1) Cutting a magnesium sheet into a disc with a handle by laser, wherein the magnesium sheet is a commercial magnesium sheet, specifically a commercial magnesium sheet produced by Dongguan Feitai Metal Products Co., Ltd., and the size of the disc is Ø16×1.5 mm, Ø8×0.5 mm and Ø6×0.5 mm, and other sizes can also be selected.
[0063] (2) Grind and polish the disc step by step with #1000 and #2000 silicon carbide papers, clean it with anhydrous ethanol, and air dry it at room temperature;
[0064] (3) The polished magnesium disc (with a supporting tail) is used as the anode, and the graphite rod is used as the cathode, which is immersed in a polytetrafluoroethylene (PTFE) container containing 46% hydrofluoric acid, and a closed circuit is formed with a DC constant voltage power supply device to start micro-arc fluorination, that is, micro-arc fluorination is carried out in a DC constant voltage mode;
[0065] (4) After the MAF process is completed, the samples are washed with deionized water and ethanol in turn and dried at room temperature.
[0066] Preferably, the conditions of the micro-arc fluorination process are: when the size of the sample disk is Ø16×1.5mm, in the constant voltage DC mode: the voltage is 185~210V; further preferably, it can be 185~195V, the current is 150~165mA, and as the diameter of the sample changes, the voltage remains unchanged, and the current decreases proportionally with the contact area.
[0067] Figure 2 The figure shows the characterization of the MAF layer: AFM images, XRD diffraction patterns, SEM scanning electron microscope images, and element distribution images of the prepared MAF samples. The characterization shows that the MAF coating is a coral-like porous structure with a thickness of 2 to 7 microns and is mainly composed of MgF2.
[0068] For other samples, the MAF coatings of other samples can be obtained by the same method. They are also coral-like porous structures with thicknesses between 0.5 and 9 microns, and the main components are also MgF2. When the preparation process is controlled under the most optimal conditions, the optimal thickness of the MAF coating is between 3 and 5 microns.
[0069] Furthermore, the method for preparing the FAP layer further includes:
[0070] (1) Immerse the MAF layer in a NanoHAP suspension. The concentration of the suspension can be determined according to the amount of crystal seed layer that needs to be adsorbed and deposited.
[0071] Specifically, a 2% NanoHAP deionized water dispersion may be preferred, and a dispersant of 1% gelatin may be added.
[0072] (2) Soak the MAF sample in the NanoHAP dispersion for 5-60 minutes, take it out, wait for the surface level to evaporate, and then immerse it in the mineralization solution for mineralization. The immersion time can be determined according to the concentration of the suspension and the amount of the crystal seed layer that needs to be adsorbed and deposited.
[0073] The FAP morphology in the present invention can be adjusted according to the composition of the mineralization solution, the mineralization time, and the mineralization temperature. Specifically, the present invention prepares two types of FAP layers on the MAF layer:
[0074] One of them is that the FAP nanorods are basically parallel to the surface of the MAF layer to assemble FAP-P, and the synthesis conditions are: After the NanoHAP seeds are deposited, they are grown in the mineralizing solution at 12-17°C for 2-8 hours, then washed with deionized water and dried at room temperature. Preferably, the NanoHAP seed deposition is repeated 3 times, the immersion time of each deposition is 15 minutes, the temperature is preferably 15°C, and the growth time in the mineralizing solution is 3 hours.
[0075] The mineralization solution formula is shown in Table 1, containing 5 ppm fluorine (added by sodium fluoride reagent). The prepared FAP and MAF double-layer coating is recorded as: FAP-P / MAF.
[0076] Another morphology is that the FAP nanorods are basically vertical to the MAF surface to assemble FAP-V. The synthesis conditions are: after the NanoHAP seeds are deposited, they are grown in the mineralizing solution at 20-90°C for 2-8 hours, then washed with deionized water and dried at room temperature. Preferably, the NanoHAP seeds are deposited once, the immersion time of the deposition is 30 minutes, the temperature is preferably 37°C, and the growth time in the mineralizing solution is 3 hours.
[0077] Table 1 Mineralizing fluid components and ratios
[0078] Element mM Mass (g / L) <![CDATA[CaCl2•2H2O]]> 1 0.147 <![CDATA[KH2PO4]]> 4 0.540 KCl 16 1.200 <![CDATA[NH4Cl]]> 4.5 0.241 HEPES 20 4.766 <![CDATA[MgCl2•6H2O]]> 0.2 0.04
[0079] The mineralization solution formula is shown in Table 1, containing 5 ppm fluorine (added by sodium fluoride reagent). The prepared FAP and MAF double-layer coating is recorded as: FAP-V / MAF.
[0080] like Figure 3 and Figure 4 Shown is the characterization of the prepared FAP-P / MAF and FAP-V / MAF coatings, where SEM, XRD, and FTIR show that two FAP layers with different morphologies were synthesized, and the coatings and the porous MAF layer formed an inter-embedded structure.
[0081] 1. Comparative analysis of the importance of MAF process
[0082] Comparative example: Ordinary immersion fluorination process
[0083] In the traditional process, the fluoride layer is generally formed by a common immersion fluoridation process. For example, CN111973812A discloses that magnesium and magnesium alloys are immersed in hydrofluoric acid to generate a chemical conversion film MgF2. The present invention uses a common immersion fluoridation process instead of the MAF process as a comparative example. After the pure magnesium metal disc is treated by the same polishing process, it is immersed in a 46% hydrofluoric acid solution for 24 hours of fluoridation treatment to form a traditional MgF2 coating. On the traditional MgF2 coating, a NanoHAP seed deposition is performed once according to the same process conditions, the immersion time is also 30 minutes, and it is grown for 3 hours at 37°C in the same mineralizing solution (see Table 1: containing 5ppm fluorine). The results show that no FAP-V layer is formed (see Figure 5 ).
[0084] That is, if only the ordinary immersion fluorination process is used, a double-layer coating that can be mineralized and self-grown in vivo cannot be formed. In other words, the MAF process for preparing porous MgF2 coating is crucial to the formation of a double-layer self-grown coating.
[0085] In addition, if Figure 6 As shown, according to the surface scratch resistance test, it can be proved that since the FAP coating and the porous MAF layer form an interlocking structure, the interface bonding strength is further improved, laying the foundation for the stability of the self-grown coating in clinical applications.
[0086] 2. The in vitro mineralization self-growth performance of the FAP / MAF coating proposed in the present invention is as follows:
[0087] Release of fluoride ions in MAF coating: In order to simulate the complex body fluid composition in vitro, α-MEM culture medium containing sugar, amino acids, 10% fetal bovine serum albumin, and calcium and phosphate ion sources was selected as the immersion medium. By immersing the magnesium metal sample covered with MAF coating in α-MEM, the release of fluoride ions at different times was investigated ( Figure 7). The results showed that the MAF coating could continuously release fluoride ions into the surrounding culture medium, and the amount of fluoride ion release tended to increase with time.
[0088] The specific experimental method is: place a magnesium metal disk (diameter: 1.6 cm, thickness: 0.5 cm) covered with MAF coating on both sides in 2 ml of α-MEM culture medium, replace the α-MEM culture medium every 24 hours, and use ion chromatography to detect the fluoride ion content in the α-MEM culture medium at different times.
[0089] Fluoride ion promotes the mineralization and self-growth of FAP layer: In order to verify the promoting effect of fluoride on the mineralization and growth of FAP-P coating in body fluid, we first deposited the FAP-P layer on a blank glass slide and immersed it in α-MEM culture medium. Then, 0.5mM NaF was added or not added to the α-MEM culture medium to confirm the promoting effect of fluoride ion on the mineralization and growth of FAP-P.
[0090] like Figure 8 As shown in the figure, after adding 0.5 mM NaF, the FAP-P coating grew and became a dense coating, while the morphology of the coating without adding fluoride did not change significantly, indicating that trace fluoride ions can promote the growth and densification of the FAP-P coating.
[0091] 3. The in vitro self-growth and densification properties of FAP / MAF coatings based on magnesium-based metals are as follows:
[0092] (1) For FAP-P / MAF coating:
[0093] The magnesium metal FAP-P / MAF coating was immersed in α-MEM culture medium containing sugar, amino acids, and 10% fetal bovine serum albumin, and its morphological growth process was as follows Fig. 9 As time goes by, the gaps in the coating are gradually filled by newly grown minerals, forming a dense morphology.
[0094] In addition, as the mineralization self-growth and densification occur, the FAP in the coating gradually matures, and more characteristic peaks of FAP appear in the XRD characterization ( Fig.10 A), Fluoride ions released from the MAF layer are internalized into FAP-P along with mineralization growth.
[0095] (2) For FAP-V / MAF coating:
[0096] The magnesium metal FAP-V / MAF coating was immersed in α-MEM culture medium containing sugar, amino acids, and 10% fetal bovine serum albumin, and its morphological growth process was as follows Fig.11As time goes by, the area near the MAF in the FAP-V coating is gradually filled with newly grown minerals, forming a dense morphology at the bottom of the FAP-V (the part marked by the yellow dotted line).
[0097] In addition, as the mineralization self-growth and densification occur, the FAP in the coating gradually matures, and more characteristic peaks of FAP appear in the XRD characterization ( Fig.12 A), Fluoride ions released from the MAF layer are internalized into FAP-V along with mineralization growth.
[0098] 4. In vitro anti-corrosion performance of FAP / MAF coating
[0099] Electrochemical corrosion test methods such as Taffel curve and impedance curve prove that the first layer of MAF coating improves the corrosion resistance of pure magnesium ( Fig.13 A and B). Compared with the MAF coating, the corrosion resistance of FAP-P / MAF and FAP-V / MAF coatings is slightly improved ( Fig.13 A and B in the figure). The long-term immersion hydrogen evolution experiment at room temperature proves that compared with the traditional MAF coating, the corrosion resistance of FAP-P / MAF and FAP-V / MAF coatings is greatly improved ( Fig.13 The Mg ion release curve tested by long-term immersion in α-MEM medium (containing protein) further proves the great anti-corrosion advantage of FAP / MAF coating, among which the FAP-P / MAF coating with higher degree of self-growth and self-densification shows the best anti-corrosion performance ( Fig.13 The above long-term comparative tests show that the strategy of self-growth and self-densification in body fluids can help improve the long-term anti-corrosion performance of the coating.
[0100] 5. In vivo mineralization self-growth and anti-corrosion performance of FAP / MAF coating
[0101] (1) In vivo self-growth performance:
[0102] First, a mouse subcutaneous implantation model was established. After 4 weeks of in vivo culture, the mineralization self-growth and in vivo corrosion resistance of the coating were investigated using different analytical methods. Fig.14 (A).
[0103] The cross-sectional SEM test results showed that after 4 weeks of implantation, the initially highly porous FAP-P layer of the FAP-P / MAF coating transformed into a dense structure, and the internal pores were filled with newly generated minerals ( Fig.14 (middle B).
[0104] The experimental results are similar to the in vitro self-growth and self-densification process. Both the FIB-TEM bright field low-magnification and high-magnification photos show the extremely dense structure inside the FAP-P layer after 4 weeks of mineralization self-growth and the close interface connection between the FAP-P layer and the MAF layer ( Fig.14 C and D, where the interface is marked by a yellow dashed line).
[0105] The experimental results further investigated the in vivo self-growth and self-densification capabilities of the designed coating, as well as the interfacial bonding stability between the FAP-P / MAF layers. Further characterization by TEM-EDS showed that the regrown FAP-P layer contained magnesium and fluoride ions in vivo. The semi-quantitative analysis by TEM-EDS showed that the F / Ca ratio increased during the self-growth process, while the Ca / P ratio decreased, compared with the FAP-P layer before implantation. The experimental results prove that fluoride ions are involved in the self-growth process of the coating ( Fig.14 Middle F).
[0106] In addition, similar to the results of the in vitro test, after 4 weeks of implantation, the FAP-V / MAF layer showed a partially dense structure, showing a certain self-growth performance, which further proved the rationality of the design of the magnesium fluoride-hydroxyapatite double coating self-growth system and the necessity of designing the FAP morphology. Fig.15 ).
[0107] (2) Internal anti-corrosion performance
[0108] In addition, the in vivo anti-corrosion performance was evaluated by measuring the average corrosion depth of the corrosion layer displayed by SEM-EDS using ImageJ software after 1, 2, and 4 weeks of implantation ( Fig.16 A, B).
[0109] The test results show that the corrosion layer thickness of pure magnesium and magnesium metal modified by MAF coating gradually increases over time. After 4 weeks of implantation in the body, the corrosion thickness of pure magnesium reaches 40μm. Traditional MAF coating gradually fails over time, and the depth of the corrosion layer reaches 6.8μm after 4 weeks of implantation, even exceeding the thickness of the MAF layer itself.
[0110] The FAP-P / MAF coating with self-growth and self-densification capabilities showed the strongest corrosion resistance, with an average corrosion depth of 0.73 μm after 4 weeks of implantation. Under the protection of the FAP-P layer, the MAF layer only had slight local corrosion.
[0111] The corrosion resistance of the FAP-V / MAF layer with a partially dense structure is also higher than that of the MAF coating, reaching a corrosion layer depth of 2.71 μm. The SEM-EDS characterization of the corrosion layer shows that the corrosion layer composition of each group is similar, with a high content of P and O elements. These test results show that the in vivo mineralization self-growth method of the double-layer protective coating proposed in the present invention can achieve satisfactory corrosion resistance in a complex environment in the body.
[0112] The above embodiments describe the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for in vivo mineralization self-growth of a double-layer protective coating, comprising a double-layer protective coating based on magnesium-based metal, wherein the first layer of the double-layer protective coating is a mineralization-promoting factor release layer, and the second layer is a mineral growth-promoting layer, characterized in that: After the magnesium-based metal double-layer protective coating is implanted in the human body, the mineralization factor in the mineralization factor release layer is released into the body fluid environment, promoting the biomineralization of calcium and phosphorus in the body fluid environment, and continuously depositing and mineralizing in the mineral growth promotion layer, and converting into new minerals. The new minerals continuously fill the defects in the second layer, and finally form a stable and dense coating in the corrosive body fluid.
2. The in vivo mineralization self-growth method of a double-layer protective coating according to claim 1, characterized in that: The mineralization promoting factor is fluoride ion, the first mineralization promoting factor releasing layer is a porous MAF layer formed on the surface of magnesium-based metal by micro-arc fluorination MAF process, and the second mineral growth promoting layer is a fluorohydroxyapatite FAP layer.
3. A double-layer protective coating for the in vivo mineralization self-growth method as claimed in claim 1 or 2, characterized in that: The first layer is the mineralization factor release layer, and the second layer is the mineral growth promotion layer.
4. The double-layer protective coating according to claim 3, characterized in that: The mineralization promoting factor release layer is a porous MAF layer formed on the surface of the magnesium-based metal by a micro-arc fluorination MAF process, and the mineral growth promoting layer is a fluorohydroxyapatite FAP layer.
5. The double-layer protective coating according to claim 4, characterized in that: The MAF layer is a coral-like porous structure with a thickness of 0.5 to 9 microns and its main component is MgF2.
6. The double-layer protective coating according to claim 4, characterized in that: In the fluorohydroxyapatite FAP layer, the FAP nanorods can assemble FAP-P parallel to the surface of the MAF layer, or the FAP nanorods can assemble FAP-V perpendicular to the surface of the MAF layer, and the FAP layer and the MAF layer form an inter-embedded structure.
7. A method for preparing a double-layer protective coating according to any one of claims 4 to 6, wherein the specific process is as follows: (1) Preparation of MAF layer: A porous MAF layer is formed on the surface of magnesium-based metal through the MAF process. The main component of the porous MAF layer is MgF2. (2) Preparation of FAP layer: Nanoapatite NanoHAP seed crystals are adsorbed on the surface of the MAF layer and placed in a mineralizing solution. The adsorption amount of the seed crystals, the temperature and time of the mineralization reaction are controlled to control the formation of a FAP layer microstructure on the MAF layer.
8. The method for preparing the double-layer protective coating according to claim 7, characterized in that: The method for preparing the MAF layer also includes: (1) Using laser to cut magnesium sheet into a disc with a handle; (2) Grind and polish the disc step by step, clean it with anhydrous ethanol, and air dry it at room temperature; (3) The polished magnesium disk with a support tail was used as the anode and the graphite rod was used as the cathode, which were immersed in a polytetrafluoroethylene (PTFE) container filled with hydrofluoric acid and subjected to micro-arc fluorination in a DC constant voltage mode; (4) After the MAF process is completed, the samples are washed with deionized water and ethanol in turn and dried at room temperature.
9. The method for preparing a double-layer protective coating according to claim 7, characterized in that: The method for preparing the FAP layer also includes: (1) Immersing the MAF layer into a suspension of nanoapatite NanoHAP; (2) The MAF sample was soaked in the NanoHAP dispersion for 5-60 min, then taken out and immersed in the mineralization solution for mineralization after the surface level evaporated.
10. The method for preparing a double-layer protective coating according to any one of claims 8 to 9, characterized in that: In the fluorohydroxyapatite FAP layer, the FAP nanorods are parallel to the surface of the MAF layer to assemble FAP-P, or the FAP nanorods are perpendicular to the MAF surface to assemble FAP-V; Among them, the synthesis conditions for assembling FAP-P with FAP nanorods parallel to the surface of the MAF layer are as follows: after the deposition of the nanoapatite NanoHAP seeds, they are grown in the mineralizing solution at 12-17°C for 2-8 hours, then washed with deionized water and dried at room temperature; The synthesis conditions for assembling FAP-V with FAP nanorods perpendicular to the MAF surface are as follows: after the deposition of the nanoapatite NanoHAP seeds, they are grown in a mineralizing solution at 20-90° C. for 2-8 hours, then washed with deionized water and dried at room temperature.
Citation Information
Patent Citations
Hydroxyapatite-containing biomaterial useful in medical implantology, biotechnology, tissue culture and pharmaceutics comprises calcium phosphate and calcium carbonate and a matrix of extracellular organic polymers
DE10143410A1
Fluorine-substituted apatite coating on surface of biologic medical magnesium or alloy thereof and preparation method
CN101703797A
Surface coating for magnesium alloy intra-bony fixing products and preparation method thereof
CN103505763A
Method for preparing medical magnesium alloy surface coating
CN106544714A
Titanium alloy implant composite material and preparation and application thereof
CN106902390A